Rapid Capillary Zone Electrophoresis of Recombinant Erythropoietin by the Use of Dynamic Double Layer Coating. (1st November 2020) - Gao, Tie; Li, Xiang; Jia, Zeng; Hendrickx, Filip; Falmagne, Jean-Bernard; Chen, Hong-Xu
Abstract: The determination of erythropoietin (EPO) isoforms by using capillary zone electrophoresis (CZE) has been a key study in the quality control of erythropoietin products. However, the current European Pharmacopeia method has been reported to provide poor reproducibility, tedious preconditioning, long separation times exceeding 60 min, and the employment of toxic reagents. In this study, a novel rapid CZE method, in which a double layer dynamic coating technique was developed for the determination of erythropoietin isoforms by the minimization of protein adsorption to the inner capillary walls and to accelerate the throughout of the protocol. The results obtained by the measured procedure were demonstrated to meet the European Pharmacopeia requirements. Real samples from different vendors were also analyzed. This rapid CZE method was shown to be suitable for the quality control (QC) erythropoietin with better reproducibility and higher sample throughput.